Prototipe Kotak Pengingat Minum Obat - Irjayanto, Sulis; Chamim, Anna Nur Nazillah (Semesta Teknika, 2015)
Patient adherence to long-term therapy of chronic diseases in developing countries less than 50%, including in Indonesia. Patient compliance is required to achieve therapeutic success, especially in the treatment of non-infectious diseases. Such as diabetes, hypertension, asthma, cancer, mental disorders, infectious diseases HIV / AIDS, and tuberculosis. One factor led patience to the non-compliance is their busyness, so they often forget to take medication. Prototype of medication reminder box is one of the solutions to remind patients to take medication on time. In previous researches, the medication reminder operated in android platform. But, gadgets equiped with android operating system are often in out of reach of many people in developing countries. So, in this study, the medication reminder box was built with alarm facility that can be regulated by the patient. This device is also used as a portable drugs storage, so that the patient can carry easily. This prototype of medication reminder box operates well as expected and supported with battery which its endurance is 24,7 hours.